3,5-Dichloro-salicylaldehyde. - Azizul, I.; Ng, S.W. (International Union of Crystallography, 2008)
THE TITLE COMPOUND (SYSTEMATIC NAME: 3,5-dichloro-2-hydroxy-benzaldehyde), C(7)H(4)Cl(2)O(2), crystallizes as discrete mol-ecules, the conformation of which may be influenced by an intra-molecular hydr-oxy-carbonyl O-H⋯O hydrogen bond.